Jacques Derrida : opening lines - Hobson, Marian (Critics of the twentieth century (London, England), 1998)
In Jacques Derrida: Opening Lines, Marian Hobson gives us a thorough and elegant analysis of this controversial and seminal contemporary thinker. Looking closely at the language and the construction of some of Derrida's philosophy, Hobson suggests the way he writes, indeed the fact he writes in another language, affects how he can be understood by English speakers. This superb study on the question of language will make illuminating reading for anyone studying or engaged with Derrida's philosophy.